The exclusion of the unworthy heir and the bureaucratization imposed by the brazilian legal order (Research, Society and Development, 2022)
The Civil Code governs several acts of Brazilians, including contracts of various kinds, liability and the way in which an heir receives the inheritance, which is called inheritance law. The present work deals with the inheritance law that has as its object the transfer of the patrimony of a deceased person to his heirs and focuses on the bureaucracy imposed by the Brazilian legal system for the exclusion of the unworthy heir of the succession. The choice of theme was due to the observance of affront to constitutional principles and characteristics such as solidarity and family trust by the imposition of Declaratory Action of Indignity in cases of indignity already confirmed in the criminal sphere. As a result of this scenario, the following problem arose: What are the possible legal consequences with the inclusion of article 1815-A by the bill 7.806/10 in the civil code in relation to the exclusion of the heir for indignity? In order to do so, the above PL was analyzed, as well as its motivations evidenced by its author (former senator Serys Slhessarenko) and compared with the current reality of exclusion for indignity after conviction in the criminal field, in addition, doctrinal positions were highlighted for being related to the scenario that seeks the PL. The conclusion was that the approval of bill 7,806/10 would enshrine the effectiveness of constitutional provisions, as well as being of relevance for the protection of important bases of the family institute and would rule out the succession of a merely patrimonial nature, its approval being essential. Finally, the methodology was carried out through analytical research carried out in doctrines, legislation and scientific articles.